Analysis of the Structure and Properties of As-Built and Heat-Treated Wire-Feed Electron Beam Additively Manufactured (WEBAM) Ti–4Al–3V Spherical Pressure Vessel - Andrey Chumaevskii; Sergey Tarasov; Denis Gurianov; Evgeny Moskvichev; Valery Rubtsov; Nikolay Savchenko; Aleksander Panfilov; Alexander M. Korsunsky; Evgeny Kolubaev (Metals)
In the present work, a high-pressure spherical vessel was fabricated from Ti–4Al–3V titanium alloy using wire-feed electron beam additive manufacturing and characterized for tightness at high pressure. Studies have been carried out to characterize the microstructures and properties of the vessel’s material in four states: as-built (BM), annealed at 940 °C with cooling in air (HT1 treatment), quenched in water from 940 °C (HT2 treatment), and quenched with subsequent annealing at 540 °C (HT3 treatment). The microstructure of the as-built (BM) samples was composed of grain boundary α-Ti and α/β lath colonies located within the columnar primary β-Ti grain boundaries. The ultimate tensile strength of the as-built material was in the range of 582 to 632 MPa, i.e., significantly lower than that of the source Ti–4Al–3V alloy wire. The subtransus HT1 heat treatment allowed β→α″ transformation, while both HT2 and HT3 resulted in improved tensile strength due to the transformation of β-Ti into α/α′-Ti and the decomposition of α′ into α/β structures, respectively.